Comparative analysis of the intestinal microbiota of black−necked cranes (Grus nigricollis) in different wintering areas - Wang, Zhongbin; Zhang, Erhao; Tang, Ying; Wu, Jiujiu; Muhammad, Suliman; Shang, Peng; Zong, Cheng; Rong, Ke; Ma, Jianzhang (Frontiers in Cellular and Infection Microbiology, 2024)
Fecal microbiota is essential for host health because it increases digestive effectiveness. The crane species Grus nigricollis (G. nigricollis) is considered to be near threatened. The fecal microbial composition of crane is less understood, particularly in the Tibet, China. This study was performed to investigate the differences in fecal microbial composition and diversity of crane in different wintering areas using third-generation single-molecule real-time sequencing technology in the Tibet, China. According to the findings, 20 samples were used to generate 936 bacterial amplicon sequence variants (ASVs) and 1,800 fungal ASVs, only 4 bacterial ASVs and 20 fungal ASVs were shared in four distinct locations. Firmicutes were the dominant bacterial phylum in all samples, and Ascomycota and Basidiomycota were the dominant fungal phylum. At the genus level, Lactobacillus was the dominant genus in Linzhi City (LZ), Shannan City (SN), and Lasa City (LS), whereas Megamonas was the dominant genus in Rikaze City (RKZ). Naganishia and Mycosphaerella were the dominant fungal genera in SN and RKZ. Mycosphaerella and Tausonia were the dominant fungal genera in LZ. Naganishia and Fusarium were the dominant fungal genera in LS. And the fecal microbial composition varied between the four groups, as shown by the underweighted pair-group method with arithmetic means and principal coordinates analysis. This study offers a theoretical basis for understanding the fecal microbial composition of crane.